Desenvolvimento de uma sistem??tica para acompanhamento de alunos e egressos sob a perspectiva da gest??o de projetos - Teixeira, Gislaine Cristina dos Santos (2015)
CAPES is the Brazilian Federal Agency for the Support and Evaluation of Graduate Education which has been contributing to the development of graduate studies in Brazil, through its system of evaluation. Lately, CAPES signaled the importance of following the professional performance of the alumni as a way to measure the quality of courses. However, researchers suggest that there are many difficulties associated with alumni??s monitoring, including the complexity of compiling a large amount of isolated and outdated data, also the lack of interest of alumni in Higher Education Institutions (HEI) evaluative processes. These barriers justify the investment in innovative projects that enable HEI to collect data and effectively monitor their alumni. In the educational setting, as in all others, the growth and dynamic of market, the competition for resources and the difficulty of combining actions and outcomes constitute the starting point of an approach oriented to projects. In this sense, the Project Management shows itself as a prominent tool for increasing efficiency. The literature provides several models and standard approaches to Project Management, but the idea of factors applicable to all projects has been severely questioned, because projects differ from one another. In this scenario, the contingency approach is an alternative. Considering the particularities of management in HIE and the need to follow the trajectory of graduate students, it is necessary to properly plan and develop an educational project of this nature, in order to obtain the best result. Thus, this study aims to answer the following question: "How to apply the Project Management to develop a systematic for monitoring students and alumni in graduate studies programs? Their objective was to develop, from the contingency approach, the design for a Systematic for Monitoring Students and Alumni in graduate studies programs. This scientific research had a qualitative approach, exploratory and descriptive nature and it was conducted by the action research method, which consists of research and action to engage in a process of identifying problems, seeking solutions, in an interactive way. The main results show that the development of the Systematic may contribute to the following aspects: (1) allow the coordination of the course effectively evaluate their program's contribution to society; (2) support CAPES with new requirements assessment for students and alumni; (3) contribute to more fruitful interaction between students and alumni, regardless of the course period; (4) demonstrate that the Project Management can be used to develop educational projects, mainly from the contingency approach, because that methodology considers the influence of the specific environment through entire project planning and execution. It is a necessary adaptation when we are dealing with projects developed by universities, which are admittedly complex organizations.